Labour law and communitarian legal standards - Jašarević Senad (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2014)
The recently adopted amendments to the Labour Code was accompanied by an extremely high resistance. While opponents consider amendments to the Law a big step back and point out that it is completely contrary to the standards of the International Labor Organization, advocates of the changes have emphasized the progressiveness. The most important argument to them was that the Code represents a substantial harmonization of our legislation with the advanced standards of EU law. Much of what have excelled both advocates and opponents of legal change is not actually correct. The main reason for the erroneous views was lack of knowledge of comparative and international labor standards. The law on the one hand is a step backwards when it comes to the protection of workers. On the other hand, it is a step forward it is a reform of the system of labor relations that was necessary and was forced by the international environment, from which our country in the era of globalization can not be excluded. Amendments to the Labour Code we see as a tendency to be in Serbia finally to establish a similar legal environment in the domain of work, as in the advanced countries of Western Europe.